Content Analysis of Beauty Product Reviews on Tiktok @tasyafarasya in Promoting Audience Consumption Behavior - Zalfa Khansa Ainiyyah; Khaerudin Imawan; Aghnia Dian Lestari (Siber Nusantara Research, 2026)
The development of social media, particularly TikTok, has driven an increase in the production and consumption of beauty product review content by influencers. This content not only serves as a source of information but also has the potential to shape consumer behavior through persuasive messages presented visually and narratively. This study aims to analyze the characteristics of beauty product review content uploaded by the TikTok account @tasyafarasya and to understand audience responses to this content. This research uses a descriptive qualitative approach. Data were collected through observation of TikTok content, interviews, and supporting documentation, then analyzed through stages of reduction, presentation, and conclusion drawing, with triangulation to test the validity of the data. Research results show that the content of beauty product reviews by @tasyafarasya has characteristics of persuasive messages structured through source credibility and the use of persuasive language that is relatable to the audience's daily life. Audience responses indicate attention, understanding, and initial positive attitudes related to emerging interest and tendencies toward consumptive behavior, although this does not always lead to a purchase.